When kidney transplantation is not an option: Haemodialysis patients' and partners' experiences-A qualitative study - Christina Egmose Frandsen; Erik Bo Pedersen; Hanne Agerskov (Wiley, 2020)
Abstract Aim To investigate the experiences and perspectives of everyday life among patients on lifelong haemodialysis and their partners. Design A qualitative exploratory study with a phenomenological-hermeneutic approach. Method Data were collected through individual interviews. In total, five patients in haemodialysis and their partners were included in the study. Data were analysed with inspiration from Ricoeur's theory around narratives and interpretation on three levels: naïve reading, structural analysis and critical interpretation and discussion. Data was collected between February 2018-June 2019. Results Limitations caused by the disease and time‐consuming treatment influenced daily life. In particular, the partners needed to have time on their own. Knowledge about the disease and participation in treatment were significant to both patients and partners. There were considerations about illness progression. Relationships to their social networks and healthcare professionals were a significant and important part of daily life for both parties.